Pembelajaran PJOK Materi Bola Basket di Masa Pasca Pandemi Covid-19 di SMA Kabupaten Pati - Moh Sabih Ainur Ridlo; Ipang Setiawan (Universitas Negeri Semarang, 2022)
This study uses a quantitative descriptive method with a survey approach. The analysis used is descriptive statistics. The purpose of this study was to determine and describe the planning, implementation and evaluation of learning physical education, sports and basketball material after the COVID-19 pandemic in Pati district high school. Pati, namely the percentage of learning planning carried out by the teacher is included in the